Influence of Job Embeddedness and Resilience on Turnover Intention in Dental Hygienists - Ji-Min Hwang; Ji-Hyoung Han (The Korean Society of Dental Hygiene Science, 2020)
Background: Maintaining a skilled workforce by minimizing the turnover of competent dental hygienists is very important for securing dental competitiveness. Therefore, it is necessary to find a predictor of turnover and lower turnover intention. To understand dental hygienist turnover, it is necessary to study the resilience, a positive factor of personal characteristics and job embeddedness that induces residual tissue. The purpose of this study was to investigate the effect of dental hygienists' job embeddedness and resilience on turnover intention.Methods: A survey was conducted on licensed dental hygienists nationwide, from March 19 to July 19, 2020. T-test and one way ANOVA analysis were performed to compare the job embeddedness, resilience, and turnover intention according to the general characteristics. Pearson's correlation analysis was performed to identify the correlation between job embeddedness, resilience, and turnover intention. Multiple regression analysis was performed to determine the effect on the turnover intention.Results: Job embeddedness was the highest with link and resilience scoring 3.57 and 4.16, respectively. The turnover intention scored 3.53. Among the general characteristics, age, marriage, total dental clinic career, education degree, and position showed statistically significant differences in job embeddedness, resilience, and turnover intention. Suitability, link, and sacrifice of job embeddedness were shown to affect the degree of turnover intention, with an explanatory power of 26.2%.Conclusion: In order to reduce the dental hygienists' turnover intention, job embeddedness and resilience should be increased. Thus, measures should be undertaken for professional and systematic program development and human resources management.